SOLVING CYBER CRIME IN ONLINE BUYING AND SELLING IN CIREBON CITY IN REVIEW OF ITE LAW AND ISLAMIC LAW - Didi Sukardi; Farha Bayu Nugraha; Ubaidillah Ubaidillah; Abdul Fatakh; Leliya Leliya; Muhammad Fadel Arrizky (UIN Siber Syekh Nurjati Cirebon, 2023)
AbstractIn the cybercrime crime of online buying and selling fraud, there is a case, one of which occurred in Cirebon City, so the police must solve the online buying and selling fraud cybercrime case. However, in practice, the police experienced several obstacles in its resolution. The method in this study is descriptive qualitative research with a case study approach. The data collection techniques carried out are observation, interviews and documentation. From the results of this study, it is known that the police from the Cirebon City Police, in handling criminal cases of online buying and selling fraud, carried out an investigation process by investigators. The investigation is carried out by checking the accounts of the perpetrators of online buying and selling scams to find evidence and track down the perpetrators. However, the police experienced several obstacles, from the limited special tools in uncovering criminal acts of online buying and selling fraud to the difficulty of finding evidence and tracking the perpetrators. Hence, the Cirebon City Police became less effective in solving online buying and selling fraud crimes.Keywords: Cybercrime; Scams; E-commerce.